PEMANASAN GLOBAL DAN KEANEKARAGAMAN HAYATI - Suryati, Tuti (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Global warming will have a negative impact on biodiversity. In contrast,the increase of population in the world has an effect to the need ofbiological resources for food, industry, medicine, etc. Human activitiesin several sectors, such as energy, forestry, agriculture, husbandry,and waste create a greenhouse effect. Greenhouse effects are due to arise of greenhouse gases, such as CO2 (carbon dioxide), CH4 (methane),N2O (nitrogen dioxide), PFCS (perfluorocarbon), HFCS (hydrofluoro-carbon), SF6 (sulfurhexafluoride), and H 2O (water vapor). Studiessuggest that climate change may also cause the melting of polar ice-caps, rising sea levels, and a shift of season. Global climate changewiil also have a wide range of effects on human health, including a riskof infectious disease epidemics. Therefore, climate change is a seriouslythreat for the world and it is necessary to have a global agreement tocombat the threat. In 2005, Kyoto Protocol was agreed and The CleanDevelopment Mechanism (CDM) is a the Kyoto Protocol’s mechanismaimed at helping industrialized countries meet their greenhouse gasreduction targets. The CDM is also meant to help developing countriesachieve sustainable development, including facilitating the transfer and/or development of low-emission technologies. Long term collectiveefforts are needed to combat and adapt with adverse effects of globalwarming, especially for the extinction of biological diversity.